Robot learning by visual observation - Vakanski, Aleksandar; Janabi-Sharifi, Farrokh, 1959- (John Wiley & Sons, Inc., 2017)
This book presents programming by demonstration for robot learning from observations with a focus on the trajectory level of task abstraction -Discusses methods for optimization of task reproduction, such as reformulation of task planning as a constrained optimization problem -Focuses on regression approaches, such as Gaussian mixture regression, spline regression, and locally weighted regression -Concentrates on the use of vision sensors for capturing motions and actions during task demonstration by a human task expert.